Zoledronic acid concurrent with either high- or reduced-dose palliative radiotherapy in the management of the breast cancer patients with bone metastases: a phase IV randomized clinical study - (:unkn) unknown (SPRINGER, 2010)
In this prospective study, the efficacy and safety of radiotherapy combined with zoledronic acid was evaluated. Breast cancer patients with painful bone metastases were randomized to either high- or reduced-dose radiotherapy. All patients received zoledronic acid (4 mg) every 28 days from the beginning of radiotherapy. Analgesic and pain scores in addition to visual analog score (VAS) for treatment satisfaction and whole-body bone scintigraphy were evaluated. No significant differences could be found in analgesic or pain scores and bone scintigraphy results between the groups. Our results suggest that reduced-dose radiotherapy produces similar response rates and response durations when used concomitantly with zoledronic acid.
Keywords: Bone metastasis; Breast cancer; Radiotherapy; Zoledronic acid; IN-VITRO; SKELETAL COMPLICATIONS; MULTIFRACTION RADIOTHERAPY; BISPHOSPHONATES INHIBIT; TRIAL; CARCINOMA; CELLS; APOPTOSIS; ADHESION; SINGLE